KONTEMPLASI PENDIDIKAN ISLAM BERBASIS PEMBERDAYAAN EKONOMI - Ahmad Maruf (Universitas Yudharta Pasuruan, 2019)
The contemplation of Islamic education has often been used as the basis by the pesantren to conduct Islamic education activities based on the economic empowerment of students and to guide and accompany the students. The Pesantren Sunan Kalijogo has the power that can be utilized to do economic empowerment in Santri. Pesantren that directly touches the students and becomes a medium of community empowerment in the field of societal economics. In the collection of research data, namely, in-depth interviews (indepth interview), this interview is a series of questions that researchers ask to the research subject. Participant observation (participant observation). Focus Group discussion. Document analysis. To form the economic empowerment programs Sunan Kalijogo Pesantren such as entrepreneurship programs, agriculture, fisheries, animal husbandry, livestock feed production, transportation, cooperatives and cafeteria Pesantren. The result of the research in Pesantren Sunan Kalijogo is to adjust the boarding school that has the vision and mission "excellence in Imtaq and Iptek, with national insight, innovative and Berakhlaqul Karimah, then make a curriculum based on economic empowerment, By incorporating Islamic educational values in accordance with the teachings of Islamic law and the trend in the field of economic affairs in Pesantren.